2022
DOI: 10.3390/ijms23020708
|View full text |Cite
|
Sign up to set email alerts
|

Omega-6 and Omega-3 Fatty Acid-Derived Oxylipins from the Lipoxygenase Pathway in Maternal and Umbilical Cord Plasma at Delivery and Their Relationship with Infant Growth

Abstract: Omega-3 and omega-6 fatty acids are important for neonatal development and health. One mechanism by which omega-3 and omega-6 fatty acids exert their effects is through their metabolism into oxylipins and specialized pro-resolving mediators. However, the influence of oxylipins on fetal growth is not well understood. Therefore, the objective of this study was to identify oxylipins present in maternal and umbilical cord plasma and investigate their relationship with infant growth. Liquid chromatography–tandem ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…However, progesterone cannot block infection-induced inflammation, and concerns remain regarding route administration, bioavailability, and its association with increased incidence of stillbirths [94]. Other drugs such as cytokine-suppressive anti-inflammatory drugs (CSAIDS), anti-inflammatory prostaglandin 15-deoxy-D (12,14), prostaglandin J2 (15dPGJ2), and antibody-based TNF-α biologics are being studied for their ability to modulate inflammatory pathways and influence prematurity [18]. A large gap remains in the effective prevention and treatment of preterm labor.…”
Section: Preterm Labor and Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…However, progesterone cannot block infection-induced inflammation, and concerns remain regarding route administration, bioavailability, and its association with increased incidence of stillbirths [94]. Other drugs such as cytokine-suppressive anti-inflammatory drugs (CSAIDS), anti-inflammatory prostaglandin 15-deoxy-D (12,14), prostaglandin J2 (15dPGJ2), and antibody-based TNF-α biologics are being studied for their ability to modulate inflammatory pathways and influence prematurity [18]. A large gap remains in the effective prevention and treatment of preterm labor.…”
Section: Preterm Labor and Deliverymentioning
confidence: 99%
“…A brief schema of n-3 and n-6 lipid metabolism, highlighting key downstream FAs and their subsequent bioactive metabolites (i.e., EPA, DHA). Figure copied from Thompson et al [14]. ALA, alpha-linolenic acid; EPA, eicosapentaenoic acid; DPA, docosapentaenoic acid; DHA, docosahexaenoic acid; HEPE, hydroxyeicosapentaenoic acid; DiHEPE, dihydroxy-eicosapentaenoic acid; HDHA, hydroxydocosahexaenoic acid; LA, linoleic acid; DGLA, dihomo-γ-linolenic acid; AA, arachidonic acid; LX, lipoxin; HODE, hydroxy-octadecadienoic acid; KODE, keto-octadecadienoic acid; HETrE, hydroxy-eicosatrienoic acids; LT, leukotriene.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a single report has been found reporting circulating oxylipin profiles in lactating humans [ 65 ] ( Table 3 ), and that study reported vitamin A status, not lactation or breastfeeding measures, as outcomes. A few studies have reported circulating oxylipins during pregnancy in humans [ 66 , 67 , 68 , 69 , 70 ], showing potential associations with infant growth [ 70 ] and pre-term birth [ 67 , 69 ], but have not investigated breastfeeding outcomes. More work is needed to characterize the systemic oxylipin profile in human circulation during lactation.…”
Section: Oxylipins During Lactationmentioning
confidence: 99%
“…Both ω-3 and ω-6 oxylipins are involved in the initiation and resolution of inflammatory processes [10]. In addition, some oxylipins are precursors of specialized pro-resolving and cytoprotective mediators (SPMs), in particular, ω3-derived oxylipins (resolvins, maresins, and protectins) with anti-inflammatory effects, which are involved in the resolution process following tissue injury [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%